FINANCIAL AND ECONOMIC MECHANISMS FOR CREATION OF INNOVATIVE REGIONAL CLUSTERS - T. V. Pogodina; N. V. Kuznetsov; N. M. Abdikeyev (Финансы: теория и практика, 2017)
Nowadays, the introduction of innovative business models is a factor of sustainable development of the Russian economy and its regions. One of such models is creation of clusters. The cluster approach came into widespread use in the 80s of the last century. The innovative development and understanding of the importance of the economy at the regional level made it possible to apply the cluster theory to these problems. At present, the cluster approach is regarded as one of the most effective tools for the development of national and regional economies. This is the way to allow the country to maintain the domestic industry and promote the development of entrepreneurship in the regions. Although the budget funding of the country’s industrial potential is characterized by relatively high indices it is not sufficient for the concurrent implementation of many large-scale projects, including the creation of innovative regional clusters and ensuring high rates of economic development of the country and individual regions. The paper discusses the use of the cluster approach to boost the innovative development of the region, methods for building a cluster management system, organizational and financial mechanisms for the development of a cluster. The analysis of the Russian experience in the use of innovative financial and economic mechanisms for creation and development of regional clusters made it possible to identify the main trends in the application of such mechanisms, evaluate their effectiveness and outline possible areas of improvement.